2012
DOI: 10.1177/194008291200500207
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Abundance, and Spatial Ecology of the Critically Endangered Ecuadorian Capuchin (Cebus Albifrons Aequatorialis)

Abstract: Geographically isolated from other C. albifrons taxa found east of the Andes, the Ecuadorian capuchin (Cebus albifrons aequatorialis) is a Critically Endangered primate that survives in a small number of localities in western Ecuador and extreme northern Peru. We assessed 11 forested areas in western Ecuador to determine presence/absence using a combination of onfoot searching and interviews with local informants. C. a. aequatorialis were present at seven of the sites surveyed, four of which represent new pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
7
0
5
Order By: Relevance
“…One example of a wide‐scale rapid assessment is that carried out for Cebus aequatorialis in western Ecuador [Jack & Campos, ]. This research identified known localities for species (and also many areas of extirpation), and followed up with distribution modeling to create a conservation plan for this Critically Endangered species [Campos & Jack, ].…”
Section: Discussionmentioning
confidence: 99%
“…One example of a wide‐scale rapid assessment is that carried out for Cebus aequatorialis in western Ecuador [Jack & Campos, ]. This research identified known localities for species (and also many areas of extirpation), and followed up with distribution modeling to create a conservation plan for this Critically Endangered species [Campos & Jack, ].…”
Section: Discussionmentioning
confidence: 99%
“…Cotacachi is largely at high elevation (>2,500 m) at its southern end. The BPs discussed here extend protection into the critically endangered NW cloud forest zone and upper montane forests that occur between 900-2500 m. These are the habitats preferred by the most endangered species in our study, including the primates (Jack & Campos, 2012;Peck et al, 2010) cats (Zapata-Ríos & Araguillin, 2013), and bears (Castellanos, 2011), as well as the frogs (Arteaga et al, 2016;Tapia et al, 2017), birds (Jahn, 2008;Willig & Presley, 2016) and orchids (Endara et al 2009). We recommend that the entire Bosque Protector system be extended the same protections as the SNAP system, particularly with regards to prohibition of mining.…”
Section: Discussionmentioning
confidence: 56%
“…We are uncertain about the presence of this species before the reintroduction; however, previous studies reported C. aequatorialis at nearby Cerro Azul, 12 km more north of the BR (Jack and Campos 2012). Priority regions conservation of this species were proposed by Campos and Jack (2013), and the BR is about 20 km from the fourth priority area.…”
Section: Discussionmentioning
confidence: 99%